Atypical orbital primary optic nerve sheath meningioma with severe disfiguring proptosis: an alternative surgical approach - Patrick, Sylves; Tat, Yeap Boon; Amin, Muhamad Zarif Mohd; Addenan, Maftuhim; Ab.Ghani, Shuaibah; Hanafi, Hanida (Medical Journal of Indonesia, 2023)
Primary optic nerve sheath meningioma is generally a benign tumor. In rare instances, however, the growth rate and intraocular and intracranial extensions can be highly aggressive, especially in children, leading to poor prognosis. Here, we reported a case of a 24-year-old woman who presented with left eye swelling for 3 years. This was associated with blurred vision, retrobulbar pain, and redness. On examination, the left eye was severely proptosed with complete ophthalmoplegia. Magnetic resonance imaging showed an extensive tumor occupying the whole left orbital cavity with a disfigured eyeball. However, no intracranial extension was observed. Interestingly, complete surgical excision was feasible via transconjunctival anterior orbitotomy without bone removal. The histopathological examination confirmed the diagnosis of optic nerve sheath meningioma. Adjunct radiotherapy was given. On a follow-up after 2 years, left enophthalmos with esotropia was observed.